Algerian Economic Diplomacy And The Purple Economy (El-Wahat Journal for Research and Studies, 2023)
Abstract:  The performance of Economic Diplomacy is one of the most important concerns of the state;This paper seeks to include an analysis of the possibility of investing Algerian economic diplomacy in advancing development from the side of the purple economy, As this study, aims to highlight the relationship between the independent variable (Economic Diplomacy) and the dependent variable (Purple Economy).Where a questionnaire was distributed to a sample of 65  Professors, specialized researchers in diplomacy research , and doctoral students; where the (SPSS) program, was used and as a result of this study it was found that there is a positive correlation between the two variables, in this way we concluded , the important role played by Economic Diplomacy  in the process of the transition toward the purple economy .Thus, the advancement of the Algerian economy and from it contributing to achieving economic security, which achieves the state's goals and future options. Keywords: Diplomacy, Economic Diplomacy, Purple Economy, Economic Security, Cultural tourism.  ملخص: يعتبر أداء الدبلوماسية الاقتصادية من أهم اهتمامات الدولة ؛ وتسعى هذه الورقة إلى تضمين تحليل لإمكانية استثمار الدبلوماسية الاقتصادية الجزائرية في دفع عجلة التنمية من جانب الاقتصاد البنفسجي ، حيث تهدف هذه الدراسة إلى تسليط الضوء على العلاقة بين المتغير المستقل (الدبلوماسية الاقتصادية) والمتغير التابع (الاقتصاد البنفسجي) حيث وزع استبيان على عينة قوامها 65 أستاذاً وباحثاً متخصصاً في مواضيع الدبلوماسية وكذا طلبة دكتوراه. حيث تم استخدام برنامج (SPSS) لتحليل النتائج، ونتيجة لهذه الدراسة تبين أن هناك علاقة إيجابية بين المتغيرين ، وبهذه الطريقة خلصنا إلى الدور المهم الذي تلعبه الدبلوماسية الاقتصادية في عملية الانتقال نحو الاقتصاد البنفسجي ، وبالتالي النهوض بالاقتصاد الجزائري وامكانية المساهمة في تحقيق الأمن الاقتصادي ، و تحقق أهداف الدولة وخياراتها المستقبلية.كلمات دالة : الدبلوماسية، الدبلوماسية الاقتصادية ، الاقتصاد البنفسجي، الأمن الاقتصادي، السياحة الثقافية